Educational Policy Evaluation: How Educational Assistance Affects PISA through School Resources, Teacher Learning, and Student Well- Being - Abd. Rohim Asnawi; Agus Timan; Sunarni Sunarni; Asep Sunandar; Raden Bambang Sumarsono (Jurnal Pendidikan Progresif, 2024)
Educational Policy Evaluation: How Educational Assistance Affects PISA through School Resources, Teacher Learning, and Student Well-Being. Objectives: This research aims to determine the effect of educational assistance policies provided by the government on school resources, teacher learning, and Student Well-Being conditions on PISA achievements. The simultaneous influence of school resources, Student Well-Being, and teacher learning on PISA. As well as the influence of educational assistance policies on PISA itself and through moderating school resource variables, Student Well-Being, and teacher learning. Methods: This type of research uses an explanatory type with a quantitative approach. Regency/city locations include Ponorogo, Tuban, Tulungagung, Banyuwangi, Surabaya City, and Malang City. This research took a population of high school and vocational school students in East Java Province with a sample size of 560 students with sampling using stratified random sampling, area proportional random sampling, and quota random sampling techniques. The data analysis used is SEM (Structural Equation Modeling). Findings: Education aid policies have a direct influence on school resources, teacher learning, student well-being, and PISA performance. Student well-being and teacher learning have a direct effect on PISA performance but school resources do not have a direct effect on PISA performance. The results of the indirect effect calculation show that the education aid policy has no effect on PISA through school resources and student well-being, but has an indirect effect through student well-being. The results of simultaneous direct and indirect calculations of educational assistance policies, school resources, teacher learning, and student well-being have an influence on PISA achievement. Conclusion: The educational assistance policies provided affect school resources, teacher learning performance and student well-being. School resources do not influence PISA performance, and school and learning resources do not directly influence PISA performance. Keywords: education assistance; school resources; teacher learning; student well-being; PISA.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202479